Bridging inflammation and proliferation: scRNA-seq analysis of chemotactic and growth factor signaling in mouse skin wound repair - Meng, Lingzhang; Li, Hongmian; Song, Jian; Lin, Wenxian; Mao, Xiuli; Zhang, Xiamin; Yang, Mingyue; Wu, Kezhao; Lu, Liu; Liang, Feiteng; Long, Feng; Li, Yueyong; et al. (Frontiers in Immunology, 2025)
IntroductionThe transition from inflammation to proliferation is a critical but poorly understood phase in wound healing. To elucidate the cellular and molecular dynamics of this pivotal stage, we performed single-cell RNA sequencing (scRNA-seq) on mouse skin biopsies 4 days after injury.MethodsBy employing our newly developed R packages, OptiRes for optimized clustering and TidyGenePlot for annotation, we identified 21 distinct cell types. CellChat analysis was used to identify intercellular communication clusters. Findings on chemotactic signaling through CCR5, CCR1, and ACKR1 were validated in vivo, and the functional significance was confirmed by demonstrating that inhibition of CCR pathways reduced phagocyte infiltration. ResultsOur analysis revealed a dynamic shift in cellular composition, characterized by an influx of neutrophils, classical monocytes, and M1 macrophages. This recruitment of phagocytes was driven by enhanced chemotactic signaling through CCR5, CCR1, and ACKR1. Furthermore, CellChat analysis identified four distinct intercellular communication clusters, highlighting the early activation of VEGF and EGF signaling pathways, which are essential for angiogenesis and re-epithelialization. DiscussionTogether, these findings provide a high-resolution map of the cellular and molecular landscape during the transition from inflammation to proliferation, offering novel insights into the mechanisms that orchestrate tissue repair and identifying potential intervention manner to enhance wound healing.